STUDI KASUS PENGEMBANGAN PELAYANAN KESEHATAN AKUPUNKTUR DI RSUD TEBET PROVINSI DKI JAKARTA PASCA PELATIHAN AKUPUNKTUR TAHUN 2016 - Gabe Gusmi Aprilla (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
One of the Government's efforts to develop traditional integrated health services in hospitals and community health centers is to conduct training for doctors working in hospitals and government-owned community health centers. From 2013 to 2018 the Ministry of Health held acupuncture training for 203 doctors who served in 160 Government-Owned General Hospitals, 1 Army Hospital, 41 Community Health Centers and 1 Health Service Unit owned by the Ministry of Health. For DKI Jakarta Province, there are already 6 doctors trained on duty at 4 public health centers and 2 Regional Hospitals owned by the DKI Jakarta Regional Government. One of the hospitals that have been trained in 2016 is Tebet General Hospital with class D type. At present the Tebet Regional Hospital has not yet developed acupuncture services since doctors were trained to complete training in 2016 due to lack of hospital management support. In developing acupuncture services in hospitals, good knowledge, attitudes and motivation are needed so that trained doctors can communicate effectively through discussion. Trained doctors also need to expand social networks in order to obtain information about the development of acupuncture services in government-owned hospitals that have already been implemented. And attend additional training in acupuncture to increase the motivation of doctors to follow the credential process at the hospital according to applicable regulations.Keyword: acupuncture health services, knowledge, attitudes, communication, training, network